Treatment Outcomes in Patients with Polypoidal Choroidal Vasculopathy - ÖZDEMİR, MEHMET HAKAN; Muslubas, Isil Sayman; Hocaoglu, M; Arf , S; ÖZDEMİR, MEHMET HAKAN; Karacorlu, M (My University, 2016)
Objectives: To report outcomes of photodynamic therapy (PDT) and combined therapy with PDT and intravitreal bevacizumab (IVB) in patients with polypoidal choroidal vasculopathy (PCV).